Some aspects of Paralympians' mental and emotional conditions - Petrova, E. A.; Makhov, A. S.; Savchenko, D. V.; Kovaleva, M. A. (Theory and Practice of Physical Culture, 2017)
The article presents findings of a primary survey of some aspects of the most common mental and emotional conditions experienced by Paralympians. Objective of the study was to offer practical recommendations to facilitate psychological support service to the athletes. The study was based on two questionnaire survey forms designed by the authors to analyse the key aspects of training for the Paralympic Games (by coaches` questionnaire survey form) and a variety of aspects of mental and emotional conditions experienced by the athletes prior to and during the competitions. Subject to the survey were 18 Paralympians from the Russian track-and-field national team and 10 coaches who train these athletes. The study was performed in April 2016 in Sochi when the athletes were trained for the Summer Paralympic Games in Rio de Janeiro. The survey data and analyses found that most of the subject athletes reported feeling highly fit for the contest, with the internal mental fitness for the event being associated in most of the subjects with the right perception of their own competitive fitness level. Furthermore it was found that the athletes who can correctly rate their own emotional conditions normally show increased sensitivity to fatigue in the training process and may stop training when the actual condition requires. Most of the coaches surveyed reported absolutely equal attitudes to their higher- and less-gifted trainees, albeit 30% of the coaches were found still prone to give more attention to the gifted trainees in the training process and show negative attitudes to failures of their trainees.